Multistimuli‐Responsive Self‐Organized Liquid Crystal Bragg Gratings. Issue 9 (18th February 2019) - Chen, Ran; Lee, Yun‐Han; Zhan, Tao; Yin, Kun; An, Zhongwei; Wu, Shin‐Tson
Abstract: A simple approach is described to fabricate an electrically, thermally, and optically responsive polarization Bragg grating, using a dual‐frequency liquid crystal (LC) doped with a photosensitive azobenzene chiral compound. Due to the employed dual‐frequency LC, the Bragg reflection is switchable by an electric field. Based on the trans ‐ cis isomerization of the azobenzene chiral dopant, the reflection wavelength of the LC Bragg gratings can be tuned across the visible wavelength by UV exposure. Meanwhile, the temperature responsivity of LC Bragg gratings is also characterized. Good agreement between experiment and theory is obtained. The circular polarization selectivity and external field tunability of LC Bragg gratings enrich these multifunctional devices and pave the way toward novel smart electro‐optical devices. Abstract : A self‐organized reflective polarization Bragg grating with electrical, photo, and thermal stimuli responsivities is proposed, based on a dual‐frequency liquid crystal host incorporated with a photosensitive chiral dopant and a chiral compound. The device possesses several unique properties, such as high diffraction efficiency, circular polarization selectivity, electrically switchable capability, and photo and thermal tunabilities.